An Anion−π Interaction Strongly Stabilizes the β‑Sheet Protein WW - Smith, Mason S; Lawrence, Eliza E. K; Billings, Wendy M; Larsen, Kimberlee S; Bécar, Natalie A; Price, Joshua L (ACS chemical biology, 2017)
Anions have long been known to engage in stabilizing interactions with electron-deficient arenes. However, the precise nature and energetic contribution of anion−π interactions to protein stability remains a subject of debate. Here, we show that placing a negatively charged Asp in close proximity to electron-rich Phe in a reverse turn within the WW domain results in a favorable interaction that increases WW conformational stability by −1.3 kcal/mol.